2012
DOI: 10.1007/s10616-012-9456-z
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated fat cells differentiate into osteoblasts in titanium fiber mesh

Abstract: Mature adipocyte-derived dedifferentiated fat (DFAT) cells rapidly differentiate into osteoblasts under three-dimensional culture conditions. However, it has not been demonstrated that DFAT cells can differentiate into osteoblasts in a rigid scaffold consisting of titanium fiber mesh (TFM). We examined the proliferation and osteogenic differentiation ability of DFAT cells using TFM as a scaffold. DFAT cells derived from rabbit subcutaneous fat were seeded into TFM and cultured in osteogenic medium containing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…When examined for their differentiation potentials in vitro, DFAT cells exhibit differentiation similar to their ASC counterparts. For example, all-trans retinoic acid can induce the osteogenic differentiation of DFAT cells [399] and increased osteocalcin expression and calcium deposition is observed when DFAT cells are seeded onto titanium fiber meshes [400]. Moreover, osteogenically induced DFAT cells are also capable of forming osteoid when subcutaneously implanted in athymic mice [396].…”
Section: Dedifferentiated Fat Cells (Dfat)mentioning
confidence: 99%
“…When examined for their differentiation potentials in vitro, DFAT cells exhibit differentiation similar to their ASC counterparts. For example, all-trans retinoic acid can induce the osteogenic differentiation of DFAT cells [399] and increased osteocalcin expression and calcium deposition is observed when DFAT cells are seeded onto titanium fiber meshes [400]. Moreover, osteogenically induced DFAT cells are also capable of forming osteoid when subcutaneously implanted in athymic mice [396].…”
Section: Dedifferentiated Fat Cells (Dfat)mentioning
confidence: 99%
“…Furthermore, subcutaneous transplanted DFAT cells formed ectopic osteoid tissue in C57BL/6N mice in vivo only with all- trans retinoic acid. Kishimoto et al 43 demonstrated rabbit derived DFAT cells differentiated into osteoblasts in a rigid scaffold consisting of titanium fiber mesh, providing an experimental basis for bone regeneration therapy.…”
Section: Multipotent Capacity Of Dfat Cellsmentioning
confidence: 99%
“…Among recent studies to explore DFAT cells, specific purification steps to insure the purity of the initial culture of mature adipocytes has seldom been reported [4][5][6][7][8][9][10]. Indeed, 96%-100% purity of isolated mature adipocyte samples utilizing fluorescence activated cell sorting (FACS), immunostaining or confocal microscopy was reported in several studies [1,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%